The expulsion of Augusta Dejerine-Klumpke from the Salpêtrière Hospital: Pierre Marie's revenge - Igor Vieira de Vieira; Emerson Luis Batista Filho; Matheus Gomes Ferreira; Carlos Henrique Ferreira Camargo; Léo Coutinho; Olivier Walusinski; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
Augusta Dejerine-Klumpke was ahead of her time, with extensive contributions to the field of neuroanatomy and neurology, achieving international recognition. Despite her great contribution to world neurology, she was expelled from the Salpêtrière hospital in 1917, due to the rivalry and mutual hatred between Pierre Marie and his rival Jules Déjerine, her husband and collaborator.